Iskul bukol : 20 years after Ungasis and Escaleras adventure - Sotto, Vic; Sotto, Tito; De Leon, Joey; Agoncillo, Ryan; Ilacad, Orly; Sotto, Marvic C.; Tuviera, Anotonio P. (2009)
The first of the one-hour-and-a-half sitcoms, it chronicled the ups and downs of collage life in the fictional Wandbol University, where storylines ran chiefly around the doings of campus hooligans in the persons of half-siblings Tito (Tito Sotto) and Joey Escalera (Joey De Leon) that make probinsiyano Victorio Ungasis (Vic Sotto) miserable.